Evaluating Hand Function in Clients with Trigger Finger - Danit Langer; Adina Maeir; Michael Michailevich; Shai Luria (Occupational Therapy International)
Background. Trigger finger (TF) is a common hand pathology frequently encountered in hand clinics. Occupational therapists predominantly assess TF symptoms as opposed to using standardized hand functioning assessments. The purpose of this study was to assess the construct validity of dexterity and grip strength assessments for clients with TF. Method. Sixty-three participants with TF and 66 healthy controls were administered the Functional Dexterity Test (FDT), Purdue Pegboard Test (PPT), and Jamar® Hydraulic Hand Dynamometer (JD) and completed the Disabilities of Arm Shoulder and Hand questionnaire (DASH). TF symptoms were graded using the Quinnell classification. Results. Statistically significant differences were found between the groups in dexterity and grip strength. A statistically significant difference between the three TF grades was found on the PPT. All three test scores were moderately correlated with the DASH scores. Conclusion. This study provides innovative evidence for the validity of common hand function assessments for individuals with TF and recommends incorporating these tools in clinical practice. Further research is needed with larger samples and better representation of each TF clinical grade.